Built‐In‐Homojunction‐Dominated Intrinsically Rectifying‐Resistive Switching in NiO Nanodots for Selection‐Device‐Free Memory Application. (19th December 2016) - Sun, Zhong; Wei, Linlin; Feng, Ce; Miao, Peixian; Guo, Meiqi; Yang, Huaixin; Li, Jianqi; Zhao, Yonggang
Abstract : Intrinsically rectifying‐resistive switching (IR‐RS) has been regarded as an effective way to address the crosstalk issue, due to the Schottky diodes formed at the metal/oxide interfaces in the ON states to suppress the sneak current at reverse biases. In this paper, the authors report for the first time another type of IR‐RS that is related to the built‐in homojunction. The IR‐RS study is usually limited to macroscopic samples with micrometer‐order pad‐type electrodes, while this work is on NiO nanodots fabricated with ultrathin anodic‐aluminum‐oxide templates and acting as nanoscaled analogs of real devices. The NiO nanodots show high storage density and high uniformity, and the IR‐RS behaviors are of good device performances in terms of retention, endurance, switching ratio, and rectification ratio. The feasibility of the IR‐RS for selection device‐free memory application is demonstrated by calculating the maximum crossbar array size under the worst‐case scenario to be 3 Mbit. Abstract : NiO nanodots fabricated with ultrathin anodic aluminum oxide templates show typical intrinsically rectifying‐resistive switching behaviors, which are exclusively attributed to the built‐in isotype homojunction induced by oxygen migration. Under the worst‐case scenario, the maximum crossbar array size is calculated to be as large as 3 Mbit. This work demonstrates the superiority of NiO for memory applications.